Avalição do desempenho logístico de cadeias produtivas agroindustriais: um modelo com base no tempo de ciclo - Costa, Eugênio José Saraiva Câmara (2002)
In the past two decades enterprises have been forced to adopt a more effective control of theirs logistics performance both in activities which depends on their own as in those linked to the supply chain they take part of. In performance assessment tasks, indicators are crucial to make feasible the evaluation process, which must show in what degree the enterprise’s stated objectives are being reached. The broad scope and the high complexity of the logistics performance evaluation process make necessary to use a due simplification on its modeling. This work presents a performance assessment model focused on the agribusiness supply chains, making use of Petri nets technique. A case study is presented and discussed concerning the melon in naturain the Agropólo Baixo Jaguaribe, a fruit production region supported by irrigation and situated in Ceará State, northeastern Brazil. The melon fruit is presently the main export fruit in Brazil and Ceará is the second larger exporter state. The proposed model is mainly based on the lead time variable and makes easily possible to visualize and to understand the performance involved with the dynamic structure analyzed in the melon supply chain. It was found that Petri nets technique may be useful in decision -taking process through the construction of scenarios and analyses of simulated courses of action. The model application results duly replicates real outputs in the case study.